Non allergic gastrointestinal manifestations of hereditary alpha-tryptasemia - Vainer, Dylan; Peterson, Kathryn (Frontiers in Allergy, 2025)
Hereditary alpha-tryptasemia (HαT) is an autosomal dominant genetic trait characterized by elevated basal serum tryptase due to increased TPSAB1 gene copy numbers. Affecting approximately 4%–6% of the Caucasian population, HαT is associated with mast cell-mediated symptoms, including cutaneous reactions, anaphylaxis, and functional gastrointestinal (GI) disorders. While the prevalence of HαT in various disorders of gut brain interaction (DGBI)is unknown, individuals with HαT exhibit GI disturbances. Mast cells, present throughout the GI tract, release mediators like histamine and prostaglandins, affecting gut motility, secretion, and permeability. Mast cell mediated activation of protease-activated receptors may contribute to gut barrier dysfunction, exacerbating the gastrointestinal symptoms. HαT-related GI symptoms are commonly misdiagnosed as other GI conditions, highlighting the need for increased awareness and further research into its pathophysiology and clinical impact. There are no randomized controlled trials on therapy for HαT mediated GI symptoms. Current treatment options are based on expert opinion, observational studies, and case reports. Effective therapies parallel those given for clonal mast cell disorders, primarily consisting of antihistamines and mast cell stabilizers. Further research is necessary to delineate the pathophysiology of HαT in the gastrointestinal tract so that targeted therapies may be developed. Herein, we aim to describe the pathophysiology, clinical manifestations, diagnostic features, and current/future therapeutic options for patients suffering from HαT-mediated GI symptoms.